La estimulación temprana y su incidencia en el desarrollo de la motricidad fina de las niñas y niños de preparatoria, primer grado de educación general básica del centro educativo integral Lago Agrio Ceila de la parroquia Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos. Período lectivo 2013-2014 - Andrango Chasipanta, Cristina Alexandra (2014)
This thesis refers to " EARLY STIMULATION AND ITS IMPACT ON THE DEVELOPMENT OF FINE MOTOR GIRLS AND BOYS HIGH SCHOOL, FIRST DEGREE GENERAL EDUCATION BASIC EDUCATION CENTER COMPREHENSIVE SOUR LAKE " CEILA" Loja NEW PARISH, SOUR LAKE CANTON, SUCUMBÍOS province. LECTIVO PERIOD 2013-2014 "conducted according to the provisions of the Regulation of Academic Board of the National University of Loja. Raised as General Objective: To sensitize the Master he and Parents about the importance of early stimulation on the Development of Fine Motor girls and boys High School , First Grade General Education Basic. The methods used for the preparation of this research work were: Scientist, Inductive- Deductive, Analytic - Synthetic, Descriptive and Statistical Model, which served them help efficiently achieve the goal. The techniques and instruments used were a survey of teachers of children from School, First Grade Students General Integral Education " CEILA " Lago Agrio Education Center, in order to establish early stimulation activities engaged in daily work, and an Observation the same for girls and boys High Schoo , First Grade General Education Basic Education Center Integral Lago Agrio" CEILA " was applied to assess the Fine Motor Development . We conclude that: 100% of teachers surveyed planned activities to encourage children First-Year Basic Education as songs, games, and 67% graph - visual techniques and stories. From which it follows that all activities aimed at stimulating the children in preschool enhance the full potential, skills and abilities in each of their areas, be they physical, intellectual, motor, personal and social, whose aim is to strengthen the interpersonal encounter between the child and the adult. 56% of surveyed children perform each and every one of the proposed activities, demonstrating their Fine Motor skills with the application of techniques such as: Thread, The Torn Cotton pellets clipping scissors and stitched or technique threading, earning a rating of Very Satisfactory, Satisfactory 37, and 7% Unsatisfactory. Fine Motor implies precision, efficiency, harmony and action, what we call gifted useful sense movements, whose implementation is related to the intervention of eye, hand, feet and face.